Pengaruh Financial Literacy, Financial Technology dan Digital Marketing Terhadap Kinerja Usaha UMKM pada Era Teknologi - Farahiyah, Qistina; Haryadi, Bambang (Universitas Muhammadiyah Gresik, 2024)
This research aims to examine the influence of financial literacy, financial technology and digital marketing on MSME business performance in the technological era in Gresik Regency. This type of research is quantitative research with an associative approach. The sampling technique in this research was a probability sampling method with the type of sampling carried out being simple random sampling. The number of respondents used was 100 respondents using a questionnaire. The data was processed and analyzed using multiple linear regression analysis techniques with SPSS version 21 software. The results of this research show that: (a) financial literacy has a significant positive influence on MSME business performance. (b) financial technology does not have a significant influence on MSME business performance. (c) digital marketing does not have a significant influence on MSME business performance. The results of this research suggest that the government should provide socialization and education regarding technology, especially regarding financial literacy, financial technology and digital marketing to MSMEs and MSMEs should take part in training or learning related to fintech because we have entered a digital era where it is no longer possible to avoided. Therefore, MSME players must be technologically literate if they want to survive and continue to develop.